1974
DOI: 10.1136/bmj.3.5924.155
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year survey of treatment with implanted cardiac pacemaker.

Abstract: Since the first implant of an artificial cardiac pacemaker in a patient by Senning in 1958 the reliability of apparatus has increased considerably and the indications for long-term pacing have greatly extended. In this paper Aetiology Thirty-two patients (8-6%) had associated ischaemic heart disease as judged by cardiac infarction, angina, or E.C.G. evidence before the onset of heart block though this was not proved to be the cause of the block. Thirty patients (8%) probably had high block in the atrioventri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1975
1975
1999
1999

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…The m~in indication for pacing in this series was syncope cir near~syncope which affected almost 90% of patients. This finding concurs with that of other large series (Sowton'et al;1974). Approximately two-thirds of these patients had documented permanent/paroxysmal cOlllplete heart block.…”
Section: Discussionsupporting
confidence: 92%
“…The m~in indication for pacing in this series was syncope cir near~syncope which affected almost 90% of patients. This finding concurs with that of other large series (Sowton'et al;1974). Approximately two-thirds of these patients had documented permanent/paroxysmal cOlllplete heart block.…”
Section: Discussionsupporting
confidence: 92%
“…Analysing the figures from 21 authors (Edhag and Lagergren, 1969;Witte et al, 1969;Fishman et al, 1970;Goldman et al, 1970;Seling and Sykosch, 1970;Shepard et al, 1971;Dixon et al, 1972;Imparato and Kim, 1972;Conklin et al, 1973;Homan van der Heide et al, 1973;Kantrowicz et al, 1973;Linschoten et al, 1973;McLaughlin et al, 1973;Mascarenhas and Center, 1973;Seremetis et al, 1973;Torresani et al, 1973;Codini et al, 1974;Sowton et al, 1974;Uhrenholdt et al, 1974;Williams et al, 1974), each of whom have reported 10&800 implantations in the past 5 years, the mean figure for surgical complications is 5.1 per cent in 7205 implants. (This incidence may be an underestimate as not all the reports indicated whether they included skin necrosis with infection.)…”
Section: Discussionmentioning
confidence: 99%
“…This is accompanied by local pain, occasionally severe, which is aggravated by deep breathing or pectoral muscle movement (3,7). Surgical intervention is needed to prevent pressure necrosis and extrusion of the generator through the skin (3,7,8).…”
Section: Impending Pacemaker Extrusionmentioning
confidence: 99%